How to make the most of history and literature in the teaching of medical humanities: the experience of the University of Geneva. Issue 1 (15th June 2005) - Louis-Courvoisier, M; Wenger, A
Abstract : In this paper the authors discuss the benefits of history and literature in the teaching of medical humanities. They suggest that human sciences produce a common effect, which they call distancing . Distancing is the awareness that one natural way to describe a given situation does not exist and that any point of view—scientific or not—is context dependant and culturally shaped. Distancing is important to medical students, by allowing them to become aware of the specificity of their own professional point of view. The authors offer a reflection on the specificities of both historical and literary approaches and on the tools they provide for medical students. This paper assumes there is a close link between the theoretical debate on the benefits provided by human sciences and the concrete framework of a given programme. The authors describe team teaching, which has been the solution adopted in the School of Medicine at the University of Geneva to obtain the most from history and literature.